Smooth ZnO:Al-AgNWs Composite Electrode for Flexible Organic Light-Emitting Device - Wang, Hu (Nanoscale Res Lett, 2017)
The high interest in organic light-emitting device (OLED) technology is largely due to their flexibility. Up to now, indium tin oxide (ITO) films have been widely used as transparent conductive electrodes (TCE) in organic opto-electronic devices. However, ITO films, typically deposited on glass are brittle and they make it difficult to produce flexible devices, restricting their use for flexible devices. In this study, we report on a nano-composite TCE, which is made of a silver nanowire (AgNW) network, combined with aluminum-doped zinc oxide (ZnO:Al, AZO) by atomic layer deposition. The AgNWs/AZO composite electrode on photopolymer substrate shows a low sheet resistance of only 8.6 Ω/sq and a high optical transmittance of about 83% at 550 nm. These values are even comparable to conventional ITO on glass. In addition, the electrodes also have a very smooth surface (0.31 nm root-mean-square roughness), which is flat enough to contact the OLED stack. Flexible OLED were built with AgNWs/AZO electrodes, which suggests that this approach can replace conventional ITO TCEs in organic electronic devices in the future.